The Effect of Public Accounting Firm Reputation, and the Previous Year's Audit Opinion on the Audit Opinion Going Concern - R. Wedi Rusmawan Kusumah; Ichsan Dwi Ramayadi; Muhammad Rohim (Universitas Pendidikan Ganesha, 2023)
Going Concern Audit Opinion is an opinion given by the auditor regarding the company's ability to continue operating for a reasonable period of time. In this context, the study aims to analyze the effect of Public Accounting Firm Reputation and Previous Year's Audit Opinion on Going Concern Audit Opinion that occurs in several companies by looking at the last five years' financial statements and seeing whether the company can maintain its business continuity in the future. or not in consideration of the reputation of the Public Accounting Firm and the Previous Year's Audit Opinion and the Acceptance of Going Concern Audit Opinion. The population in the study was 21 companies. The sampling method used was purposive sampling so that samples were obtained as many as 14 companies during the 5-year observation period so that it became 70 samples. This type of research is quantitative research, the data analysis technique used is Logistic Regression using the EViews 10 tool. The results of this study show that the Reputation of Public Accounting does not affect the Going Concern Audit Opinion, then the Previous Year's Audit Opinion has a significant effect on the Going Concern Audit Opinion of the Previous Year and the Acceptance of the Going Concern Audit Opinion.